Altered regulatory mechanisms governing cell survival in children affected with clustering of autoimmune disorders - Palamaro, Loredana (BioMed Central, 2012)
Clustering of Autoimmune Diseases (CAD) is now emerging as a novel clinical entity within monogenic immune defects with a high familial occurrence. Aim of this study is to evaluate the regulatory mechanisms governing cell survival, paying a particular attention to Fas-induced apoptosis, in a cohort of 23 children affected with CAD. In 14 patients, Fas stimulation failed to induce cell apoptosis and in 1 case it was associated with Fas gene mutation. Our study highlights the importance to evaluate cell apoptosis in the group of children with CAD, which, with this regard, represents a distinct clinical entity.